Pollen‐induced allergic rhinitis in 1360 Italian children: Comorbidities and determinants of severity. Issue 8 (17th November 2013) - Dondi, Arianna; Tripodi, Salvatore; Panetta, Valentina; Asero, Riccardo; Businco, Andrea Di Rienzo; Bianchi, Annamaria; Carlucci, Antonio; Ricci, Giampaolo; Bellini, Federica; Maiello, Nunzia; Miraglia del Giudice, Michele; Frediani, Tullio; et al.
Abstract Background Pollen‐induced allergic rhinoconjunctivitis (AR) is highly prevalent and rapidly evolving during childhood. General practitioners may not be fully aware of the nature and severity of symptoms experienced by patients and might underestimate the prevalence of moderate or severe disease. Thus, the relevance of early diagnosis and intervention may be overlooked. Objectives To investigate the severity of pollen‐induced AR and its determinants in Italian children referred to allergy specialists and who had never received specific immunotherapy (SIT). Methods Children (age 4–18 yr) affected by pollen‐induced AR who had never undergone SIT were recruited between May 2009 and June 2011 in 16 pediatric outpatient clinics in 14 Italian cities. Recruited children's parents answered standardized questionnaires on atopic diseases (International Study of Allergy and Asthma in Childhood, Allergic Rhinitis and its Impact on Asthma, Global Initiative for Asthma). The children underwent skin‐prick test (SPT) with several airborne allergens and six food allergens. Information on socio‐demographic factors, parental history of allergic diseases, education, perinatal events, breastfeeding, nutrition and environmental exposure in early life was collected through an informatics platform shared by the whole network of clinical centers (AllergyCARD™). Results Among the 1360 recruited patients (68% males, age 10.5 ± 3.4 yr), 695 (51%) had moderate‐to‐severe AR, 533 (39%) asthma, and 325 (23.9%) oral allergy syndrome (OAS). Reported onset of pollen‐induced AR was on average at 5.3 ± 2.8 yr, and its mean duration from onset was 5.2 ± 3.3 yr. Only 6.2% of the patients were pollen‐monosensitized, and 84.9% were sensitized to ≥3 pollens. A longer AR duration was significantly associated with moderate‐to‐severe AR symptoms (p 0.004), asthma (p 0.030), and OAS comorbidities (p < 0.001). Conclusions This nationwide study may raise awareness of the severity of pollen‐induced AR among Italian children who have never received pollen SIT. The strong association between pollen‐induced AR duration and several markers of disease severity needs replication in longitudinal studies, while suggesting that countrywide initiatives for earlier diagnosis and intervention should be planned.